Analisis of Digital Information Media for Education in the Purwodadi Botanic Garden Using Analytical Hierarchy Process - Rachmawan Adi Laksono; Hari Ginardi R.V. (IPTEK Journal of Proceedings Series, 2020)
Purwodadi Botanical Garden is an ex-situ plant conservation institution. According to Presidential Regulation No. 93 of 2011 the Botanical Gardens have the duties of conservation, research, education, environmental services. Wisata Flora is an educational package conducted by Purwodadi Botanical Garden, the activity depends on the Wisata flora tour guide and the information boards in the garden. The availability of tour guides is still limited, and the information boards supporting Wisata Flora are also limited. This was obtained from interviews with visitors who use the Purwodadi Botanical Gardens education service. Therefore, we need a breakthrough in the way of delivering information to support flora tourism activities by utilizing digital technology. Digitalization is an environmentally friendly alternative compared to through the addition of information in physical form. Some of the technologies that exist today can be used as an alternative delivery of information to visitors independently, namely Quick Response (QR) Codes, RadioFrequency Identification (RFID), and Location Based Service (LBS). Of the three alternatives required a priority of application in accordance with the needs and management capabilities of Purwodadi Botanical Gardens. The research will be conducted using the quesioner and interview method with the management of Purwodadi Botanical Gardens and analyzed using the Analytical Hierarchy Process method. The results of the analysis are expected to be valuable input for the management of Purwodadi Botanical Gardens.